Stephania tetrandra and Its Active Compound Coclaurine Sensitize NSCLC Cells to Cisplatin through EFHD2 Inhibition - Shu-Yu Hu; Tsai-Hui Lin; Chung-Yu Chen; Yu-Hao He; Wei-Chien Huang; Ching-Yun Hsieh; Ya-Huey Chen; Wei-Chao Chang (MDPI AG, 2024)
Background: Adjuvant chemotherapy, particularly cisplatin, is recommended for non-small cell lung carcinoma (NSCLC) patients at high risk of recurrence. EF-hand domain-containing protein D2 (EFHD2) has been recently shown to increase cisplatin resistance and is significantly associated with recurrence in early-stage NSCLC patients. Natural products, commonly used as phytonutrients, are also recognized for their potential as pharmaceutical anticancer agents. Result: In this study, a range of Chinese herbs known for their antitumor or chemotherapy-enhancing properties were evaluated for their ability to inhibit EFHD2 expression in NSCLC cells. Among the herbs tested, Stephania tetrandra (S. tetrandra) exhibited the highest efficacy in inhibiting EFHD2 and sensitizing cells to cisplatin. Through LC-MS identification and functional assays, coclaurine was identified as a key molecule in S. tetrandra responsible for EFHD2 inhibition. Coclaurine not only downregulated EFHD2-related NOX4-ABCC1 signaling and enhanced cisplatin sensitivity, but also suppressed the stemness and metastatic properties of NSCLC cells. Mechanistically, coclaurine disrupted the interaction between the transcription factor FOXG1 and the EFHD2 promoter, leading to a reduction in EFHD2 transcription. Silencing FOXG1 further inhibited EFHD2 expression and sensitized NSCLC cells to cisplatin. Conclusions: S. tetrandra and its active compound coclaurine may serve as effective adjuvant therapies to improve cisplatin efficacy in the treatment of NSCLC.